Effect of Spinning Triangle and Production Speed of Hollow-Spindle System on the Bouclé Yarn Structure - Malek Alshukur (University of Ljubljana, Faculty for Natural Sciences and Engineering, 2021)
This study aims to show the impact of both the width of the base of the spinning triangle and the production speeds of hollow-spindle spinning machines on the structure of ultimate multiple-thread-structure bouclé yarns and similar fancy yarns. A hollow-spindle spinning machine was used and bouclé yarns were made of a core thread, an effect thread and a (multifilament) binder. Initially, five bouclé yarns were made by setting the widths of the base of the spinning triangle at five levels, i.e. 4.5 mm, 7.5 mm, 10 mm, 13 mm and 16 mm. A further six bouclé yarns were made to show the changes that occur to the spinning triangle at various production speeds. The resulting fancy bouclé yarns were assessed by measuring the size, number and circularity ratio of bouclé profiles. It was found that at low production speeds, i.e. at start-up, that the spinning triangle was unstable, which adversely affected the structure of the final bouclé yarns. However, at production speeds higher than 17 m/min, the spinning triangle became stable, though such a stable spinning triangle had no impact on the structure of the resulting fancy bouclé yarns. The results of this study may help fancy yarn manufacturers to avoid making defective fancy yarns.